2015
DOI: 10.1128/mbio.01021-15
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Biofilms Induce Macrophage Dysfunction Through Leukocidin AB and Alpha-Toxin

Abstract: The macrophage response to planktonic Staphylococcus aureus involves the induction of proinflammatory microbicidal activity. However, S. aureus biofilms can interfere with these responses in part by polarizing macrophages toward an anti-inflammatory profibrotic phenotype. Here we demonstrate that conditioned medium from mature S. aureus biofilms inhibited macrophage phagocytosis and induced cytotoxicity, suggesting the involvement of a secreted factor(s). Iterative testing found the active factor(s) to be prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
145
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 151 publications
(152 citation statements)
references
References 88 publications
5
145
0
2
Order By: Relevance
“…1 and 2, respectively) and thus was not considered biologically significant. UAMS-1 and LAC were utilized for all subsequent dose-response studies, since UAMS-1 originated from an orthopedic infection and we have a great deal of knowledge about the behavior of LAC in the orthopedic-implant model (25)(26)(27)40). This approach was further justified by the finding that MW2 behaved similarly to both UAMS-1 and LAC in terms of immune profiles and biofilm burdens.…”
Section: Resultsmentioning
confidence: 99%
“…1 and 2, respectively) and thus was not considered biologically significant. UAMS-1 and LAC were utilized for all subsequent dose-response studies, since UAMS-1 originated from an orthopedic infection and we have a great deal of knowledge about the behavior of LAC in the orthopedic-implant model (25)(26)(27)40). This approach was further justified by the finding that MW2 behaved similarly to both UAMS-1 and LAC in terms of immune profiles and biofilm burdens.…”
Section: Resultsmentioning
confidence: 99%
“…This may be explained by either additional targets that are recognized by this toxin, cellular targets not reconstituted in this model, and/or multiple conflicting effects of the LukAB/CD11b interaction. In a murine model of joint infection, LukAB and α-toxin were expressed together in biofilms, facilitating S. aureus growth and suppression of macrophage function [41], suggesting activity toward murine macrophages. However, single lukAB mutants have been shown to have a phenotype in a mouse renal abscess model [42] but not in models of bacteremia or rabbit skin and abscess formation [43].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been suggested that, as with cancer, "remission" is a more appropriate term than "cure" in the context of osteomyelitis (2). Several factors contribute to this therapeutic recalcitrance, including the inability to diagnose the infection before it has progressed to a chronic stage in which the local vasculature is compromised, the formation of a bacterial biofilm that limits the efficacy of both conventional antibiotics and host defenses, the emergence of phenotypic variants within the biofilm (persister cells and small-colony variants) that exhibit metabolic traits that limit their antibiotic susceptibility, and the ability of the pathogens involved, including S. aureus, to invade and replicate within host cells, including osteoblasts (3)(4)(5)(6)(7)(8)(9). Collectively, these factors dictate that the clinical problem of osteomyelitis extends far beyond acquired resistance and the increasingly limited availability of effective antibiotics.…”
mentioning
confidence: 99%